If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2X + 6 = 5X + -1(X + -8) Reorder the terms: 6 + 2X = 5X + -1(X + -8) Reorder the terms: 6 + 2X = 5X + -1(-8 + X) 6 + 2X = 5X + (-8 * -1 + X * -1) 6 + 2X = 5X + (8 + -1X) Reorder the terms: 6 + 2X = 8 + 5X + -1X Combine like terms: 5X + -1X = 4X 6 + 2X = 8 + 4X Solving 6 + 2X = 8 + 4X Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-4X' to each side of the equation. 6 + 2X + -4X = 8 + 4X + -4X Combine like terms: 2X + -4X = -2X 6 + -2X = 8 + 4X + -4X Combine like terms: 4X + -4X = 0 6 + -2X = 8 + 0 6 + -2X = 8 Add '-6' to each side of the equation. 6 + -6 + -2X = 8 + -6 Combine like terms: 6 + -6 = 0 0 + -2X = 8 + -6 -2X = 8 + -6 Combine like terms: 8 + -6 = 2 -2X = 2 Divide each side by '-2'. X = -1 Simplifying X = -1
| x-0.3x=8.96 | | 6-3=14 | | 7x+2y=4fory | | 75+0.5x=30 | | 6+(-1)-3-[(-2)-(-5)2]= | | 4f^2+18f=10 | | x^3-3x-50=0 | | -2f(2f-4)=-4(f+2) | | 3m=44 | | 4x+6y=9 | | z^2+11z=-18 | | (2x*2)+(4*2)=(3x*2)+(2x) | | x^2+12x=-21 | | -7*1= | | z(z-3)(2z+1)=0 | | -7*-1= | | 2x*2+4*2=3x*2+2x | | 2n^2+5n+7=0 | | 50x=300 | | 6x-5=2x-5x | | 2m+3m(m-8)=1 | | 3t^2+4t+21=0 | | 6-3-4=2+x | | 2x*2+8*2=3x*2+2x | | .05(.3m+35n)-.8(-.09n-22)= | | 2(x+3)+x=4(-3) | | -5-r=10 | | f(x)=x^2+6x+18 | | 8x+3(2-3x)=25 | | 194-2x=43x+19 | | 24x^2+24x=0 | | 27+(4x-30)+(3x-10)+x=360 |